Development of boron carbide concrete for enhanced radiation shielding in nuclear reactors - P. Gokul; J. Ashok Kumar; R. Preetha; Sudipta Chattopadhyaya; Pew Basu; M. Menaka; V. Subramanian; B. Venkatraman; Dhanya Sathyan; K. Jayanarayanan; Mini K. Madhavan (Case Studies in Construction Materials)
Concrete is widely utilized as a radiation shielding material fortified by its neutron attenuation property, affordability, mouldability, easy availability and strength characteristics. This study examined the effectiveness of incorporation of Boron Carbide (B4C), a material renowned for its neutron attenuation properties as a fine aggregate replacement in concrete, to enhance its neutron shielding capabilities without compromising the strength. This research provides insights into the development of special concrete for radiation shielding, in diverse nuclear and medical applications. The radiation shielding concrete (RSC) was prepared by replacing fine aggregate with B4C in various percentages 5 %, 10 % and 15 %. The workability, mechanical properties and neutron attenuation characteristics of B4C admixed concrete were compared with those of ordinary concrete. Results showed that the inclusion of B4C slightly reduced workability, with a 9.5 % slump reduction in samples containing 15 % B4C. Compressive strength exhibited a minor reduction at higher B4C levels, maintaining the target strength of 30 MPa at 15 % B4C, while split tensile and flexural strength showed negligible changes. Microstructural analysis indicated a minor increase in porosity with increasing B4C content. Hence the results demonstrate a substantial improvement in neutron shielding with minimal strength reduction. Additionally, gamma shielding showed comparable performance to normal concrete. Hence, the test results demonstrated that the inclusion of Boron Carbide significantly enhances the neutron shielding performance of concrete, devoid of any compromise on the latter's integrity.